Implementation and evaluation of online and offline blended teaching model in laboratory course of Clinical Laboratory Hematology - Li, Dan; Wang, Fang; Zhou, Xiaodong; Peng, Kejun; Zhang, Limei; Yan, Hong; Li, Xiaoying; Zhang, Juan (Frontiers in Education, 2025)
This study explores the implementation and evaluation of online and offline blended teaching model in the Clinical Laboratory Hematology (CLH) laboratory course at Chengdu Medical College. To this end, 90 students majoring in medical laboratory technology in 2020 were selected as research subjects and randomly divided into experimental and control groups. The experimental group adopted an online and offline blended teaching model, while the control group adopted a traditional one. After-class tests, laboratory examinations, questionnaire surveys, and student interviews were conducted to evaluate the teaching effectiveness. The average scores of both tests and examinations in the experimental group were significantly higher than those in the control group (p < 0.05). Furthermore, the results of the feedback questionnaire showed that the satisfaction and self-evaluation of the learning effect of students in the experimental group were significantly better than those in the control group (p < 0.05). The blended teaching model has been successful and popular in CLH. This is a useful teaching mode worth applying to laboratory teaching in medical courses.